Faith as a Moral Mobilizer: A Quantitative Study of Islamic Values, Fear, and Freedom Among Muslim Student Demonstrators in Bandung - Fazilatun Nisa, Raisa Fayyaza; Lamist, Della Chintya; Mufidah, Dzakiyyah; Firmansyah, Mokh Iman (State Islamic Institute of Kudus (IAIN Kudus), 2026)
This study analyzes the relationships among Islamic spiritual values, structural fear, and freedom of expression as three central constructs shaping Muslim students' motivations and perceptions during the demonstrations. A descriptive quantitative approach was employed using a cross-sectional survey design, with data collected through an online questionnaire administered to 36 Muslim undergraduate students in Bandung who directly participated in the protests. Data was analyzed using descriptive statistics, Cronbach's Alpha reliability testing, and Pearson correlation via SPSS. Results indicate that the faith scale demonstrated acceptable internal consistency (α = 0.792), while the fear (α = 0.474) and freedom (α = 0.078) scales require further instrument refinement. Descriptively, students showed strong spiritual awareness of social injustice (mean = 4.17) and a high perception of genuine social unrest (mean = 4.36). Correlation analysis revealed a statistically significant positive relationship between faith and social activism orientation (r = 0.503, p < 0.01), while fear showed a non-significant negative association with solidarity and freedom, treated here as exploratory. These findings suggest that Islamic spiritual values function as a moral mobilizer in student activism and offer a new analytical framework for understanding faith-based collective action among urban Muslim communities in Indonesia.